Temporal and environmental correlates of carbon stocks in a regenerating tropical forest. Issue 3 (26th March 2020) - Capellesso, Elivane Salete; Cequinel, Anamaria; Marques, Renato; Marques, Marcia Cristina Mendes
Abstract: Questions: Carbon dynamics in tropical forests is influenced by a variety of biotic and abiotic factors that act over temporal and spatial scales. At the local scale, carbon stock and dynamics can be determined by the environment and ecosystem diversity. Also, during forest regeneration, which is a temporal process, it is expected that those factors that influence carbon also change over time. Here we examine how carbon stock and dynamics are influenced by forest age, environment and functional diversity during forest regeneration. Using the relative effects of the different drivers of carbon dynamics, we attempt to discern the mechanisms (mass effect or niche complementarity) that explain those processes. Location: We carried out this study in Atlantic Forest of different ages during natural regeneration in southern Brazil. Methods: We measured environmental characteristics (soil physical and chemical attributes and canopy openness), estimated functional diversity and above‐ground carbon and its dynamics over time. We examined univariate and multivariate predictors of carbon stock and dynamics using structural equation models. Results: We found that age had the strongest influence on carbon stock, while environmental characteristics, functional and taxonomic diversities were much less important or unimportant. Our results suggest that the influence of time on tropical forest carbon dynamics overlaps and outweighs the effects due to environmental limits and mechanisms mediated by diversity (mass effects, niche complementarity). Conclusions: Natural regeneration can be an effective strategy for restoring carbon sequestration and methods that use manipulation of regenerating forests with the hope of improving the process are unlikely to bring additional advantage in terms of carbon sequestration. Abstract : During tropical forest regeneration we found that forest age was the strongest influence on above‐ground carbon and carbon increase by recruitment. Environmental characteristics and diversity had a smaller or no effect. Thus, the simple passage of time should be sufficient for increasing carbon stock and dynamics in restoration initiatives whose goal is to mitigate global warming.